Demystifying risk attitudes and fertilizer use: A review focusing on the behavioral factors associated with agricultural nitrogen emissions in South Asia - Begho, Toritseju; Eory, Vera; Glenk, Klaus (Frontiers in Sustainable Food Systems, 2022)
Fertiliser use is environmentally unsustainable in South Asia. Ideally, farmers would follow optimal fertilisation rates for crops based on scientific recommendations. However, there is ample evidence on why farmers under-fertilise or over-fertilise their crops. Important amongst them is that farmers’ attitude to risk influences decisions on fertiliser use. This paper reviews studies on the effects of risk attitude on fertiliser use, the timing of application, and application intensity. We observe that the use of fertiliser is affected by perceptions of fertiliser as a risk-enhancing or risk-reducing input. To influence future fertiliser decisions of farmers, several policy measures are suggested. Among these, gradual withdrawal of fertiliser subsidies, providing enhanced-efficiency fertilisers and eliminating the fraudulent practice of fertiliser adulteration may be the most appropriate in a South Asian context.